SALIVARY INTERLEUKIN-1 AND 8-HIDROXYDEOXYGUANOSINE AND THEIR RELATION WITH THE PERIODONTAL STATUS - Aureliana Caraiane; Victoria Badea; Florin Ciprian Badea; Mircea Grigorian (Romanian Society of Oral Rehabilitation, 2014)
Aim of the study This study aims to quantify interleukin-1 (IL-1) and 8-hidroxydeoxyguanosine (8-OHdG) from saliva and to identify a possible correlation between the values of this biomarkers and the periodontal status. Material and methods We made clinical oro-dental evaluation for 40 subjects which were divided in 4 groups: healthy control, gingivitis (G), chronic periodontitis (CP) and aggressive periodontitis (AP). We collected saliva according to the recommendations of the World Health Organization and measured the quantity of the two biomarkers by using ELISA method. Results The values of both biomarkers increased progressively from healthy oro-dental status to the status of CP and AP. There are highly statistically significant differences between the amount of salivary IL-1 quantified in healthy group versus AP patients and between CP and AP (p<0.0001). There are also highly statistically significant differences between the level of 8-OHdG quantified in the saliva of healthy group compared to those with chronic and aggressive periodontitis (p<0.0001). We identified highly statistically significant differences between the level of IL-1 and 8-OHdG quantified in patients with AP (p<0.0001). Our study shows a high correlation between periodontal pocket depth and the level of 8- OHdG identified in patients with CP and AP (r=0.854, p=0.0004 for CP and r=0.708, p=0.021 for AP). Conclusions Our study demonstrates that these two biomarkers may be useful in assessing the health of the periodontium.